The role of body muscle mass as an indicator of activity in inflammatory bowel disease patients. (December 2020) - Zalizko, Polina; Roshofa, Tereze Hermine; Meija, Laila; Bodnieks, Edgars; Pukitis, Aldis
Summary: Background & aims: Malnutrition is an objective disease activity parameter for patients with inflammatory bowel disease (IBD), particularly Crohn's Disease (CD), and is an indicator of lesion expansion or inflammatory activity. Active disease is correlated with the systemic response of the body's immune system, activating a hypermetabolic state and protein degradation (Argiles JM, 2015) . These conditions lead to malnutrition, which significantly increases the risk of impaired clinical outcomes, such as delayed recovery or increased mortality (Landi F, 2019). Our aim was to identify malnutrition parameters associated with more pronounced metabolic status changes in IBD patients (i.e., classified as by low and high clinical activity) as an indicator of disease activity. Methods: This prospective pilot study included hospitalised patients aged ≥18 years, with an established diagnosis of IBD, with no medical history of surgical interventions. IBD patients were divided into those with low clinical activity indexes (CD activity index [CDAI] <150 for CD and Mayo <4 for ulcerative colitis [UC]) and those with high clinical activity indexes (CDAI >150 for CD and Mayo >4 for UC). Patients were assessed twice using the Nutritional Risk Score (NRS2002) and Malnutrition Universal Screening Tool (MUST) and 48 body bioelectrical impedance analysis (BIA) measurements were taken. A control group consisting of heathy age- and sex-matched individuals was used for comparison. Results: Fifty hospitalised patients (median age, 36.5 IQR: 28.5–51.5 years) were enrolled, of which 44% (n = 21) were female and 56% (n = 27) were male. Of these, 48% (n = 23) patients were diagnosed with CD and 52% (n = 25) with UC. The median CDAI was 128 (IQR = 6.0–207.0) and Mayo score was >4 (IQR = 1.0–8.0). The study group comprised 48% (n = 23) patients with low IBD activity and 52% (n = 25) of patients with high IBD activity. According to the NRS2002, 31% (n = 15) patients were nutritionally at risk and in need of nutritional support and an additional 24% (n = 12) had low-risk requiring observation, without necessity for additional nutritional care. According to the MUST score, 40% (n = 19) of patients had a high-risk of malnutrition requiring a nutritional care plan and 19% (n = 9) were of low-risk. Overall, 31% (n = 17) of patients received enteral oral feeding and 10% (n = 4) required additional parenteral feeding. The group with low IBD activity showed a considerably lower score on both screening tools (NRS2002 p = 0.007; MUST p < 0.001). Comparing BIA results between IBD patients and the control group, the median BMI was lower for the CD (21.10 [IQR = 19.2–23.3]) than for the control group (23.4 [IQR = 21.5–25.8]) (p = 0.014). In addition, visceral fat mass was lower in CD (−4, 00 [IQR = −12.1 to 5.6]) than in the control group (7.85 [IQR = −0.9-18.2]) (p = 0.003). In terms of deviation from standard weight, 39% (n = 9) of CD patients showed reduced %body fat, while this was observed in only 19% (n = 5) of UC patients. Reduced muscle mass was observed in 48% (n = 11) of CD patients and in 19% (n = 4) of UC patients, while only 13% (n = 6) of all IBD patients had reduced BMI. Conclusions: IBD patients with high disease activity indices had a noticeably increased risk for malnutrition (according to NRS2002 scores), taking into consideration not only IBD activity, but also increased weight loss and loss of appetite. Most CD patients in both the low and high disease activity groups had reduction in muscle mass, which was not evaluated in UC patients. Identification of the reduction in soft lean muscle mass in CD patients can be used as an anticipatory indicator of disease activity.